Effectiveness Of Digital-Based Services J-Lahbako In Population Administration - Mayasiana, Nur Aini; Riski , Maria Vincentia N. (POLITICO, 2025)
Public services based on digital technology have begun to be developed by the Indonesian government along with the implementation of digital-based governance. This study aims to analyze the effectiveness of public services using the J-lahbako application in Tempurejo Village, Tempurejo District, Jember Regency. This study uses a qualitative approach with a descriptive design. Data collection was carried out through observation, interviews, and documentation, with four informants selected using purposive sampling techniques. Data validity was tested by triangulation of sources, techniques, and time. Data analysis was carried out with the steps of data collection, data condensation, data presentation, and drawing conclusions. The theory of effectiveness is used to assess the extent to which the goals or targets set in an organization, activity, or program are achieved. An activity is said to be effective if the goals or targets that have been determined can be achieved properly. The results of the study indicate that the J-lahbako application program is right on target and effective in its use, and is very helpful for the community in managing administration. However, the socialization of this program is still limited to one meeting attended by all RT and RW in Tempurejo Village, Tempurejo District, so that many people have not utilized the services at the Tempurejo Village Office. More intensive and comprehensive socialization needs to be carried out by the Tempurejo Village government so that this information can reach the community more widely